Pleadings, Minutes of Public Sittings and Documents/Mémoires, proces-verbaux des audiences publiques et documents (2023) (International Law E-Books Online, Collection 2024., 2024)
This volume contains the texts of written pleadings, minutes of public sittings and other documents from the proceedings in the Dispute concerning delimitation of the maritime boundary between Mauritius and Maldives in the Indian Ocean (Mauritius/Maldives), Merits . The documents are reproduced in their original language. The Special Chamber delivered its Judgment on 28 April 2023. It is published in the ITLOS Reports 2022-2023 . Le présent volume reproduit les pièces de la procédure écrite, les procès-verbaux des audiences publiques et d'autres documents relatifs à la procédure concernant le Différend relatif à la délimitation de la frontière maritime entre Maurice et les Maldives dans l'océan Indien (Maurice/Maldives), fond . Les documents sont publiés dans la langue originale utilisée. La Chambre spéciale a rendu son arrêt le 28 avril 2023. L'arrêt est publié dans le TIDM Recueil 2022-2023 .